Supply chain quality management: A theoretical framework for integration measurement - MacHado, Marcio Cardoso (2016)
This paper aims to present a theoretical framework for performance measurement of supply chain quality management (SCQM). A review of the literature on supply chain quality management, supply chain and quality management was conducted to develop key performance measurements related to six areas of integration between quality management and supply chain management environment: leadership, continuous improvement and innovation, sustainability, stakeholder involvement and commitment, information, and management and strategic planning. The findings suggest that SCQM integration can be assessed by nine performance measurements. The study contributes to our understanding of quality management practices within a supply chain (SC) environment from an integrated perspective. It extends the concept of supply quality chain integration by focusing on key performance measurement that may help to improve the overall performance of the supply chain.